Generation of Pediatric Leukemia Xenograft Models in NSG-B2m Mice: Comparison with NOD/SCID Mice - Gopalakrishnapillai, Anilkumar; Kolb, E. Anders; Dhanan, Priyanka; Bojja, Aruna Sri; Mason, Robert W.; Corao, Diana; Barwe, Sonali P. (Frontiers in Oncology, 2016)
Generation of orthotopic xenograft mouse models of leukemia is important to understand the mechanisms of leukemogenesis, cancer progression, its cross talk with the bone marrow microenvironment, and for preclinical evaluation of drugs. In these models, following intravenous injection, leukemic cells home to the bone marrow and proliferate there before infiltrating other organs, such as spleen, liver, and the central nervous system. Moreover, such models have been shown to accurately recapitulate the human disease and correlate with patient response to therapy and prognosis. Thus, various immune-deficient mice strains have been used with or without recipient preconditioning to increase engraftment efficiency. Mice homozygous for the severe combined immune deficiency (SCID) mutation and with non-obese diabetic background (NOD/SCID) have been used in the majority of leukemia xenograft studies. Later, NOD/SCID mice deficient for interleukin 2 receptor gamma chain (IL2Rγ) gene called NSG mice became the model of choice for leukemia xenografts. However, engraftment of leukemia cells without irradiation preconditioning still remained a challenge. In this study, we used NSG mice with null alleles for major histocompatibility complex class I beta2-microglobulin (β2m) called NSG-B2m. This is a first report describing the 100% engraftment efficiency of pediatric leukemia cell lines and primary samples in NSG-B2m mice in the absence of host preconditioning by sublethal irradiation. We also show direct comparison of the engraftment efficiency and growth rate of pediatric acute leukemia cells in NSG-B2m and NOD/SCID mice, which showed 80–90% engraftment efficiency. Secondary and tertiary xenografts in NSG-B2m mice generated by injection of cells isolated from the spleens of leukemia-bearing mice also behaved similar to the primary patient sample. We have successfully engrafted 25 acute lymphoblastic leukemia (ALL) and 5 acute myeloid leukemia (AML) patient samples with distinct cytogenetic characteristics in NSG-B2m mice, with the purpose of generating pediatric ALL and AML xenografts for preclinical evaluation of drugs. Thus, our data support the use of NSG-B2m mouse model for leukemia engraftment and in vivo preclinical drug efficacy studies.